Persepsi kepuasan nelayan purse seine terhadap penerbitan dalam perijinan satu pintu di UPT. Pelabuhan Perikanan Pantai Bulu – Tuban - Munir, Miftachul; Suprihanto, Agus (Universitas Halu Oleo, 2024)
Fishing ports are one of the public agencies that aim to provide the best service in fulfilling the interests of the fishing community, especially fishermen as users of port facilities. The aim of this research is to determine the level of satisfaction with services and find out the service development strategy at the UPT of the Bulu Beach Fisheries Port, Tuban Regency. Issuance of BBM, STBLK (Departure) and STBLK (Arrival) Recommendation Letters. This research methodology uses a qualitative descriptive methodology with data collection techniques using questionnaires and interviews, data analysis using Miles and Huberman theory, results of interviews and questionnaires with 15 owner respondents /master of the Purse Seine ship obtained data admitting that the Purse Seine fishing gear fishermen felt very satisfied, as shown by the average variable of fuel recommendation service (X1), Departure STBL Service (X2), and Arrival STBL (X2), and service satisfaction (Y), The average percentage of Strongly Agree (SS) answers was 56%, Agree (S)=28%, with the reason that they were helped in taking care of the requirements needed to purchase fuel and the needs for going to sea or after arriving, and the average answer tone was Disagree ( TS)= 16% for the reasons: limited fuel purchases and incomplete ship documents that have not been extended, so they find it difficult to process and do not agree to give recognition